2015
DOI: 10.31129/lumat.v3i1.1049
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics teachers’ knowledge for teaching problem solving

Abstract: In recent years, considerable attention has been given to the knowledge teachers ought to hold for teaching mathematics. Teachers need to hold knowledge of mathematical problem solving for themselves as problem solvers and to help students to become better problem solvers. Thus, a teacher’s knowledge of and for teaching problem solving must be broader than general ability in problem solving. In this article a category-based perspective is used to discuss the types of knowledge that should be included in mathem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
44

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 64 publications
1
49
0
44
Order By: Relevance
“…Muhtarom, Juniati, & Siswono (2017b) explains that a large number of university pre-service students to become mathematics teachers who hold platonist views is due to their mathematics experience at school, and university courses have also strengthened these beliefs. Belief is an important thing that must be instilled in children early on as it can be the basis for disposition, the basis for action, the basis for change and the basis for learning (Chapman, 2015).…”
Section: Pujiasih 'S Knowledge and Beliefs About Mathematicsmentioning
confidence: 99%
“…Muhtarom, Juniati, & Siswono (2017b) explains that a large number of university pre-service students to become mathematics teachers who hold platonist views is due to their mathematics experience at school, and university courses have also strengthened these beliefs. Belief is an important thing that must be instilled in children early on as it can be the basis for disposition, the basis for action, the basis for change and the basis for learning (Chapman, 2015).…”
Section: Pujiasih 'S Knowledge and Beliefs About Mathematicsmentioning
confidence: 99%
“…In truth, the knowledge deals with problem-posing is one of the knowledge that is required to teach about mathematics problem-solving that should be mastered by mathematics teachers besides knowledge of problemsolving in mathematics itself. Knowledge of problem-posing needs to be mastered by mathematics teachers because through this knowledge, they are expected to have a capability in promoting problem-solving proficiency of their students by giving facilitation for students to construct the diverse and meaningful mathematics problems (Chapman, 2015). Moreover, Ellerton (2013) suggested that young teachers should be given a chance to acquire problem-posing skills and believe in their self-ability in posing mathematics problems as an effort to make themselves become capable in mathematics problem-posing and also to assist their students during the problemposing activity in mathematics learning.…”
Section: Affective Factors and Beliefsmentioning
confidence: 99%
“…More specifically, mathematics teachers need to master the knowledge of problem-solving for teaching mathematics because basically problem-solving itself is the core of teaching and learning mathematics. Such knowledge is required by mathematics teachers as problem solvers as well as to facilitate their students in attempting to be a better mathematics problem solver (Chapman, 2015). Furthermore, this knowledge is actually comprised of three classes, namely content knowledge of problem-solving, pedagogical knowledge of problemsolving, and beliefs and factors in the affective domain that may influence problem-solving.…”
Section: Introductionmentioning
confidence: 99%
“…While the focus has been given more on the students in the early years, a body of studies directly or indirectly offering recommendations of the knowledge teachers should hold to teach problem-solving is required to be developed. Therefore, in order to have a broader insight on the needs of teacher related to problemsolving, Chapman [1] has proposed the so called 'mathematics problem-solving knowledge for teaching' (MPSKT), i.e. the knowledge needed to effectively teach problem solving.…”
Section: Introduction (Heading 1)mentioning
confidence: 99%
“…Chapman [1] describes the categories of problem solving knowledge into three main categories, namely problem solving content knowledge, pedagogical problem-solving knowledge, and knowledge of affective factors related to problem-solving teaching. Problem-solving content knowledge includes four things.…”
Section: Introduction (Heading 1)mentioning
confidence: 99%